Advancing statistical literacy for prospective teachers: A systematic review of contemporary approaches and best practices - Utari, Rahma Siska; Putri, Ratu Ilma Indra; Zulkardi; Hapizah (Jurnal Elemen, 2025)
This study employs a Systematic Literature Review (SLR) to explore the development of statistical literacy among prospective teachers, which is crucial in today’s data-driven educational landscape. The review synthesizes findings from 18 selected studies published between 2015 and 2024, focusing on various pedagogical approaches, challenges in implementation, and strategies for enhancing statistical literacy instruction. Current approaches and best practices include inquiry-based learning, real-world data applications, and interactive digital tools. These approaches aim to engage prospective teachers in authentic statistical experiences, which can enhance their ability to teach statistical concepts effectively. The study identifies key themes in statistical literacy education using a comprehensive methodology that includes defining research questions and establishing inclusion and exclusion criteria. Key findings reveal four primary research themes: strategies for teaching statistical literacy, competencies needed for prospective teachers, educational contexts, and the role of technology in statistical learning. The review also identifies significant gaps in the existing literature, particularly related to effective curriculum integration and the specific challenges educators face. This SLR contributes to the ongoing discourse on educational statistical literacy, providing a foundation for future research and practical applications in teacher preparation.